2017
DOI: 10.1159/000485383
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress Activates Glial Cells in the Hippocampus but Attenuates Cytokine Secretion in Response to an Immune Challenge in Rat Pups

Abstract: Objective: Early life stress (ELS) increases the vulnerability to developing psychopathological disorders in adulthood that are accompanied by brain inflammatory processes. However, it is not known how a combined double hit (stress and immune) at an early age affects the response of the neuroimmune system. Here we investigated the effect of periodic maternal separation (MS) followed by administration of lipopolysaccharide (LPS) on glial cells in the CA3 region and hilus of the hippocampus and on cytokine relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 61 publications
3
29
2
1
Order By: Relevance
“…In male rats, MS and MD resulted in decreased GFAP reactivity and reduced cytoskeletal complexity in the hippocampus (Roque, Ochoa‐Zarzosa, & Torner, ; Saavedra, Fenton Navarro, & Torner, ) and cortex (Musholt et al, ) within 24 hr after MS or MD. Similarly, in Octodon degus , MD resulted in decreased density of GFAP + astrocytes in the cortex, associated with reduced length and ramification of astrocytic processes (Braun, Antemano, Helmeke, Büchner, & Poeggel, ).…”
Section: Ela Induced Alterations In Astrocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…In male rats, MS and MD resulted in decreased GFAP reactivity and reduced cytoskeletal complexity in the hippocampus (Roque, Ochoa‐Zarzosa, & Torner, ; Saavedra, Fenton Navarro, & Torner, ) and cortex (Musholt et al, ) within 24 hr after MS or MD. Similarly, in Octodon degus , MD resulted in decreased density of GFAP + astrocytes in the cortex, associated with reduced length and ramification of astrocytic processes (Braun, Antemano, Helmeke, Büchner, & Poeggel, ).…”
Section: Ela Induced Alterations In Astrocytesmentioning
confidence: 99%
“…At this stage, more research is necessary to elucidate the specific order of events. Interestingly, also MD/MS induced alterations on astrocytes were sometimes accompanied by activation of microglia (Réus et al, ; Roque et al, ; Saavedra et al, ). It is striking that despite the similar activation of microglia, different effects were described for GFAP, with lasting upregulation after immune challenges but no persistent changes in GFAP after MD/MS, suggesting alternative mediators and processes involved.…”
Section: Ela Induced Alterations In Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early life stress models in which mothers and pups are given access to limited amounts of bedding, result in impaired glutamate uptake by hypothalamic astrocytes (Gunn et al, 2013). Maternal separation, another early-life stress, impacts the number of astrocytes in the hippocampus (Saavedra, Fenton Navarro, & Torner, 2017). Considering the role for astrocytes in synapse formation and maturation (Allen et al, 2012;Blanco-Suarez, Liu, Kopelevich, & Allen, 2018;Stogsdill et al, 2017), impairment of astrocyte function at early stages of postnatal development should have dramatic consequences on neuronal function.…”
Section: Part Iii-conclusion and Future Directionsmentioning
confidence: 99%
“…Interestingly, there is emerging evidence that astrocytes are also implicated in effects of ES (reviewed in [33]). ES leads to immediate and permanent changes in astrocyte number and morphology [34][35][36][37][38] that may contribute to cognitive deficits. Furthermore, we have shown that ES leads to persistent alterations in microglia up to the age of 10 months.…”
mentioning
confidence: 99%